Transcriptome analysis of Harumi tangor fruits: Insights into interstock-mediated fruit quality - Liao, Ling; Li, Yunjie; Bi, Xiaoyi; Xiong, Bo; Wang, Xun; Deng, Honghong; Zhang, Mingfei; Sun, Guochao; Jin, Zhenghua; Huang, Zehao; Wang, Zhihui (Frontiers in Plant Science, 2022)
Harumi tangor fruit with Ponkan as an interstock contains significantly higher levels of total soluble solids compared to Harumi tangor fruit with no interstock. Transcriptome analysis of two graft combinations (Harumi/Hongjv (HP) and Harumi/Ponkan/Hongjv (HPP)) was conducted to identify the genes related to use of the Ponkan interstock. Soluble sugars and organic acids were also measured in the two graft combinations. The results showed that the contents of sucrose, glucose, and fructose were higher in the fruits of HPP than in those of HP; additionally, the titratable acid levels were lower in grafts with interstocks than in grafts without interstocks. Transcriptome analysis of HPP and HP citrus revealed that the interstock regulated auxin and ethylene signals, sugar and energy metabolism, and cell wall metabolism. Trend and Venn analyses suggested that genes related to carbohydrate-, energy-, and hormone-metabolic activities were more abundant in HPP plants than in HP plants during different periods. Moreover, weighted gene co-expression network analysis demonstrated that carbohydrates, hormones, cell wall, and transcription factors may be critical for interstock-mediated citrus fruit development and ripening. The contents of ethylene, auxin, cytokinin, transcription factors, starch, sucrose, glucose, fructose, and total sugar in HPP plants differed considerably than those in HP fruits. Interstocks may help to regulate the early ripening and quality of citrus fruit through the above-mentioned pathways. These findings provide information on the effects of interstock on plant growth and development.